2021
DOI: 10.25145/j.pasos.2021.19.049
|View full text |Cite
|
Sign up to set email alerts
|

A importância da marca no turismo: o caso da entidade regional do Turismo do Porto e Norte de Portugal

Abstract: In the last few decades, branding is an important part of marketing tourism destinations. Tour‑ ist destinations started to be seen as companies and started to use the brand as a way to attract and retain visitors. The brand is based on a perspective of value creation acting as a differentiation strategy in an increasingly competitive market. In this context, this study presented here sought to understand how the regional entity of Tourism in Porto and Northern Portugal has developed its marketing through bran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Residents are conscious that the development of tourism has promoted the rehabilitation of buildings that had been degraded for years, in the most well-known areas such as Ribeira and Sé. There is also agreement with the literature about a very positive view and evaluation of the social impacts of tourism as it contributes to the development of the city infrastructures in general particularly in the years pre-covid, as identified by other studies (Gomes, 2020;Silva, 2017;Martins, 2019). Caution is suggested though when interpreting these positive perceptions, as residents were likely to be influenced by low levels of visitors and inherent economic depression, caused by Covid-19.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Residents are conscious that the development of tourism has promoted the rehabilitation of buildings that had been degraded for years, in the most well-known areas such as Ribeira and Sé. There is also agreement with the literature about a very positive view and evaluation of the social impacts of tourism as it contributes to the development of the city infrastructures in general particularly in the years pre-covid, as identified by other studies (Gomes, 2020;Silva, 2017;Martins, 2019). Caution is suggested though when interpreting these positive perceptions, as residents were likely to be influenced by low levels of visitors and inherent economic depression, caused by Covid-19.…”
Section: Discussionsupporting
confidence: 75%
“…Other qualitative aspects like residents' satisfaction are researched on a rather ad hoc basis, and studies scarce, mostly conducted for academics purposes (e.g. Azevedo, 2010;Martins, 2019;Silva, 2017;) This study aim is thus to address the phenomenon of (over)tourism in Porto area, and more recently, the zero tourism: how is tourism affecting residents´ life from their own perspective?…”
Section: Sustainability In Tourism and Monitoring System In Portugalmentioning
confidence: 99%
“…All tourism logistics, such as means of transport, hospitality and catering, and local commerce make the sector a generator of investment and employment. In 2018, the WTO found that the economic recovery strengthened tourist demand in several markets, growth was notorious in Europe and Africa, presenting data higher than the world average (Martins 2019).…”
Section: Tourism Industrymentioning
confidence: 99%
“…As is the example of the change in the exchange rate, or other conjunctures that may negatively influence tourism. These inflations may result from excessive demand for goods and activities from economic operators (Martins, 2019).…”
Section: Tourism Industrymentioning
confidence: 99%